Stockhausen’s Helicopter String Quartet and the challenge of conceptual music - Juha Torvinen; Susanna Välimäki (Slovakia, 2022)
The Helicopter String Quartet (1993) by German composer Karlheinz Stockhausen (1928–2007) is one of the most notorious works of classical music of the past decades. -The work is scored for a traditional string quartet, four helicopters each with a pilot and a sound technician, audio and video communications equipment, a sound engineer (or ‘sound projectionist’) and a moderator (optional). Lasting half an hour, the work features the four musicians playing the music each in their own helicopter, in the air.
The present article discusses the work from the ‘conceptual music’ perspective.- Our approach is based above all on a musicological translation of the theory of conceptual art developed in visual arts scholarship, i.e. the application of that theory to art consisting of sound. Our analysis is based on the score of the work including its written instructions, the composer’s other commentaries on the work, the recording made by the Arditti Quartet and the documentary directed by Scheffer.- The article is a discussion of the ways in which the Helicopter String Quartet challenges our thinking about music and the world.
We first discuss the concept of conceptual music and then a feature characteristic of conceptual music in general and this work of Stockhausen’s in particular that we call a manifestation of a concept. This means presenting ideas using concrete symbols. In the work at hand, the key concepts being manifested are the concepts of air, sound direction, the world, the cosmos and light. Also, the transgressive approach of the work to the string quartet tradition prompts reflection on the relationship of the work to (chamber) music and to music as a metaphor for the miraculous and the ineffable. Finally, we discuss the Helicopter String Quartet as music that presents as a metaphor of itself and explore conceptuality as a feature of this music.